Preventing unintentional injuries in childhood in primary care - Kendrick, Denise (1997)
Unintentional injuries in childhood are a major cause of mortality and morbidity. Numerous risk factors for unintentional injury have been identified over recent years, and there have been several suggestions that injury prevention programmes should be targeted at children identified as high risk, based on these risk factors. There has also been increasing interest in, and emphasis on, the role of members of the primary health care team in preventing unintentional injuries to children, including within recent government policy. There is some evidence, so far, that primary care interventions can be effective in reducing hazards, increasing knowledge and changing behaviour. There is however, less evidence that they can be effective in reducing injury frequency or severity, with very few studies of high quality addressing this issue.